Optical properties of organic NLO chromophores for terahertz applications : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Physics at Massey University, Palmerston North, New Zealand - Kutuvantavida, Yasar (Massey University, 2012)
This thesis was motivated by the potential of organic nonlinear optical (NLO) zwitterionic chromophores to be used as active components in THz emitters and detectors. This study presents the results from measurements of the electro-optic (EO) coefficient, photostability and the THz properties of organic NLO chromophores. An EO coefficient of over 700 pm/V was measured for some EO polymers using the Teng-Man modulation ellipsometry technique at low frequencies. A roll off in the value of the EO coefficient was observed for frequencies over 10 kHz and converging to the theoretically estimated value of ∼ 2 pm/V. The large over estimate of the EO coefficient at low frequencies using the Teng-Man method is attributed to contributions from the cavity resonance and interference effects. The EO coefficient was also measured using a new method based on the electric field induced modulation of diffraction gratings. The measured EO coefficient using this technique is an order of magnitude lower than that measured using the Teng- Man method but it is an order of magnitude higher that the theoretically expected value. By investigating DC and AC measurements it was possible to deduce that the large apparent EO coefficient is due to the inverse piezoelectric effect and thin film interference. The large EO coefficient at low frequencies may also have a contribution from dipole clusters. The small EO coefficient at high frequency shows that the chromophores may not be particularly useful for THz applications. However, they have potential in low frequency applications such as modulators, and dense wavelength division multiplexing. The current photodegradation models are shown to be inadequate and the photodegradation can be modeled by considering a distribution in the photodegradation quantum efficiencies. The addition of a singlet oxygen quencher has been found to enhance the photostability of some chromophores by up to 6 times. Structural modifications also affect the photostability. A correlation between the photostability and bond length alternation (BLA) was found where there is a trade-off between the chromophores molecular NLO effect and photostability. Calculations based on the THz dielectric properties showed that the EO polymers have a reasonable coherence length for THz generation using optical rectification. Low wavenumber Raman spectroscopy measurements made on recrystallised compounds exposed some theoretically predicted modes that were not been reported found experimentally. Low temperature and low energy Raman spectroscopy measurements made on some selected organic compounds showed a strong temperature dependence of the low energy vibrational modes. The temperature dependent redshift and line broadening have been primarily attributed to thermal expansion and a distribution in the distance between monomers.
Keywords: Nonlinear optics; Chromophores; Terahertz technology; Electro-optics; Polymers